PERANCANGAN STRATEGI PEMASARAN VISUAL MELALUI MEDIA SOSIAL UNTUK MEREK DAGANG “ZOUSZ GROOMING” PADA AGENSI KREATIF LAPOMPS DI BALI - Yofandry Raffi, Raka; Sarjani, Ni Ketut Pande; Arya Putraka, Agus Ngurah (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
In the midst of the increasingly competitive business world, business people must make efforts to attract consumer interest. Seeing the development of the business world today, digital technology is part of several important means in supporting the development of a business, so that all forms of marketing activities can be recognized and accepted easily by the public at large, this is called digital marketing. The utilization of social media in digital marketing has become one of the main strategies for many companies in recent years. As a result of the development of an increasingly broad digital platform, social media management is needed in the digital marketing process so that it provides a great opportunity for companies to reach a wide audience. The Design Process of Visual Marketing Strategy through Social Media for theTrademark “ZOUSZ GROOMING” at Lapomps Creative Agency in Bali is needed to find out the process of designing social media from various countries. The methods used in the design process include interview and observation stages. The SOUZS brand can significantly increase user interaction and engagement through an effective and integrated social media design strategy. With an approach that focuses on creating relevant and engaging content, consistent management of the selected social media platforms, and in-depth analysis of audience trends and responses, it is expected that SOUZS can efficiently expand its reach and increase brand awareness in a competitive market.